Faktor yang Memengaruhi Pemilihan Metode Kontrasepsi - Rendys Septalia; Nunik Puspitasari (Universitas Airlangga, 2016)
Contraception was the most eﬀective way to control the population growth. The most widely favored in Indonesia was a short-term contraceptive methods. High attainment acceptor on short-term contraceptive methods because short-term contraceptive methods was a methods contraception aﬀordable, while the fees for the long-term contraceptive methods was more expensive. The incidence of injectable contraceptives and pills drop-out was higher than the long-term contraceptive methods that contributed to the failure of population growth control program. This study to analyze the factors that aﬀect the selection contraceptive methods. This study was an observational study with cross sectional design. Sampling with systematic random and obtained were 79 acceptors. The independent variables were the cost of contraceptive use, non-material costs (experience side eﬀects), cultural obstacle, social adjustments obstacle, physic and mental health obstacle, and accessibility obstacle. Data collected using the questionnaire and analyse by multiple logistic regression. The results showed that the signiﬁcant factor were the cost of contraceptive usage (pvalue = 0.002), the cost of non-material (experience side eﬀ ects) (pvalue = 0.007), and factors that didn’t have signiﬁ cant inﬂuence were cultural obstacle (pvalue = 0.105), social adjustments obstacle (pvalue = 0.999), physic and mental health obstacle (pvalue = 0.920), and accessibility obstacle (pvalue = 0.438). The conclusion were the cost of contraceptive use and non-material costs (experience side eﬀ ects) aﬀ ected the selection of contraception. It was need the cooperation between religious leaders, community leaders, and health care workers in a common understanding on the cost of contraceptive usage.